(untitled) (Cultura Económica, 2019)
This article shows the risks for the University’s identity in the current knowledge society. The prestigious American mathematician dead in 2005, argues that the universities in the United States have been affected by the dismantling of research industrial laboratories and their transfer to the academic area. According to Mac Lane, this and other factors like a managerialist conception of education, are deforming university research work subordinating it to the logic of short-run outcomes.